Hasil Belajar pada Mata Kuliah Asuhan Kebidanan Kehamilan Dipengaruhi Praktik di Laboratorium Kebidanan - Theresia Anita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the relationship between practical learning in the midwifery laboratory and the learning outcomes in the Pregnancy Midwifery Care Subjects of the Level II D-3 Midwifery students. This research method uses descriptive-analytic with the cross-sectional approach. The results showed that the level of practical learning in the laboratory was a high category of 59.1%. And category learning outcomes are 72.6%. Statistical test results show that the P-value = 0.029. There is a relationship between practical learning in midwifery laboratories and learning outcomes in the Pregnancy Midwifery Care Course. Keywords: Pregnancy Midwifery Care, Laboratory Practices